The system of values of the priestless Old Believers in an historical retrospective - Pociechina, Helena (Przegląd Wschodnioeuropejski, 2018)
The article discusses some problems of the sacrament of penance, connected to the system of values, contained in the text of hand written document called ‘A Rite of Confession’ from the collection of library of the nunnery of the Holy Trinity and the Savior in Wojnowo (Poland). Because the Old Believers did not recognize the jurisdiction of state authorities, considering the authorities as the embodiment of the Antichrist, all aspects of social life of the Old Believer’s community were governed by the provisions of ancient Byzantine canon law from No-mocanon and by traditional norms of ethics. The penalty for each offense was determined by confessor and could be defined by dint of the text of ‘A Rite of Confession’. The author discusses the legitimacy of using the modern approach to describing the value system with respect to historical texts.